The application of graphene and its composites in oxygen reduction electrocatalysis: a perspective and review of recent progress. Issue 2 (11th November 2015) - Higgins, Drew; Zamani, Pouyan; Yu, Aiping; Chen, Zhongwei
Abstract : This paper provides a critical review and perspective on progress realized recently towards the development of graphene-based oxygen reduction catalysts. Abstract : The pressing necessity of a sustainable energy economy renders electrochemical energy conversion technologies, such as polymer electrolyte fuel cells or metal–air batteries, of paramount importance. The implementation of these technologies at scale still faces cost and operational durability challenges that stem from the conventionally used oxygen reduction reaction (ORR) electrocatalysts. While years of progress in ORR catalyst research has yielded some very attractive material designs, further advances are still required. Graphene entered the picture over 10 years ago, and scientists have only recently achieved a level of understanding regarding how its specific properties can be fine-tuned for electrocatalyst applications. This paper provides a critical review of the knowledge generated and progress realized over these past years for the development of graphene-based ORR catalysts. The first section discusses the application potential of graphene or modified graphene as platinum nanoparticle catalyst supports. The second section discusses the important role that graphene has played in the development of non-precious metal ORR catalysts, and more particularly its role in pyrolyzed transition metal–nitrogen–carbon complexes or as a support for inorganic nanoparticles. Finally the development of heteroatom doped graphene species is discussed, as this has been demonstrated as an excellent method to fine-tune the physicochemical properties and induce catalytic activity. Throughout this paper, clear differentiation is made between acidic and alkaline ORR catalysts, and some common misconceptions or improper testing practices used throughout the literature are revealed. Synthesis strategies and how they pertain to the resulting structure and electrochemical performance of graphene are discussed. In light of the large body of work done in this area, specific strategies are suggested for perpetuating the advancement of graphene-based ORR electrocatalysts. With concerted efforts it is one day likely that graphene-based catalysts will be a staple of electrochemical energy systems.